Effect of rifampicin on the lipid profile of albino rats - DE Peters; RN Ichipi-Ifukor (Journal of Applied Sciences and Environmental Management)
The study was designed to investigate the effect of rifampicin on the lipid profile and histopathology of the heart of albino rats. Albino rats (42) were used and rifampicin was administered at 1.10mg/120g body weight (BW) and 0.55mg/120g BW for intervals of 20, 40 and 60days. Result from the study revealed that there was a significant increase (p<0.05) in triglyceride level for animals dosed with 1.10mg/120g BW - 1.08±0.07, 1.37±0.12 and 1.52±0.12 mmol/L for 20, 40 and 60days of drug administration respectively when compared to the control (0.78±0.09 mmol/L ). Also there was a significant increase (p<0.05) in triglyceride level for those dosed with 0.55mg/120g BW - 1.20±0.09, 1.46±0.09 and 1.47±0.01 mmol/L respectively for intervals of 20, 40 and 60days. There was also a significant increase P<0.05) in total cholesterol level for animals dosed with 1.10mg/120g BW ie 1.85±0.10, 2.08±0.15, and 2.10±0.18 mmol/L for 20, 40 and 60 days respectively and animals dosed with 0.55mg/120g BW ie 1.83±0.15, 2.03±0.12 and 2.05±0.10 mmol/L for 20, 40 and 60 days respectively when compared to the control (1.40±0.06 mmol/L ). There was a significant decrease in the high density lipoprotein-cholesterol level of animals dosed with 1.10mg/120g BW for 20, 40 and 60 days respectively (0.37±0.08, 0.45±0.08 and 0.45±0.10 mmol/L) and also in animals dosed with 0.55mg/120g BW (0.40±0.09, 0.42±0.07 and 0.40±0.06 mmol/L) for 20, 40 and 60 days respectively, when compared to the control value (0.68±0.07 mmol/L) at (p<0.05). Histological  examination of the heart revealed normal architectural structure of the heart after rifampicin administration for 20 and 60days, though pattern of plasma lipid alteration suggests dyslipidemia; therefore plasma lipid profile should be monitored routinely because of the positive relationship between increased dyslipidemia with cardiovascular diseases.